![\frac{3x - 2}{10} - \frac{x + 3}{7} + \frac{4x - 7}{3} = x - 1 \frac{3x - 2}{10} - \frac{x + 3}{7} + \frac{4x - 7}{3} = x - 1](https://tex.z-dn.net/?f=+%5Cfrac%7B3x+-+2%7D%7B10%7D++-++%5Cfrac%7Bx+%2B+3%7D%7B7%7D++%2B++%5Cfrac%7B4x+-+7%7D%7B3%7D++%3D+x+-+1)
Solve it.....
Answers
Answered by
0
Answer:
x = 4
Step-by-step explanation:
-
+
=
=>21(3x - 2) - 30(x + 3) + 70(4x - 7) = 210(x - 1) [multiplying both sides by 210]
=> 63x - 42 - 30x - 90 + 280x - 490 = 210x - 210
=> 103x = 412
∴ x = 4
Similar questions
History,
4 months ago
Hindi,
4 months ago
Hindi,
8 months ago
English,
8 months ago
Social Sciences,
1 year ago
Political Science,
1 year ago